Emma Izon - Thesis submitted in partial fulfilment of the degree of Doctor of Clinical Psychology (DClinPsych) - Izon, EJ (2023)
Systematic Review of the Literature: The Psychosocial Stressors of Siblings of People with Experiences of Psychosis (SOPEP): A Systematic Narrative Review across Cultures.